PELAKSANAAN PROGRAM PEMUDA SARJANA PENGGERAK PEMBANGUNAN DI PEDESAAN (PSP-3) DALAM MENINGKATKAN KEMANDIRIAN KEWIRAUSAHAAN PEMUDA DAN IMPLIKASINYA TERHADAP KETAHANAN EKONOMI WILAYAH (Studi Di Kecamatan Dlingo, Kabupaten Bantul D.I Yogyakarta) - Ramdani, Deni (Jurnal Ketahanan Nasional, 2014)
The execution of PSP3âs program was realized correctly that was touching assorted of activity component in the public that was economics, education and social. The activity of program had the character of flexible accommodating with need there in the public. The execution of program PSP3 in the region of Dlingo District faced various constraints like geographical condition, language factor and cultural, lack of a reliable source of support from local local government, fi nancing element of management of program. Programme PSP3 in the Dlingo district was not able yet to increased economic resilience in the region, because was not able yet to increased entrepreneurship independence in Dlingo District.Keywords: PSP3 Program, Entrepreneurial Self-Reliance, Economic Resilience of Region